İstanbul’da Fransız ticareti (17. yüzyıl) - Aksu, Ahmed (My University, 2024)
Bu çalışma, 17. yüzyılda İstanbul’daki Fransız ticaretini ele alarak bu yüzyıla ait Osmanlı ve Fransız kaynaklarını gün yüzüne çıkarmayı, araştırmacılara yeni çalışma alanları sunmayı hedeflemektedir. Araştırmanın amacı, Fransız ticaretinin İstanbul’da nasıl geliştiğini, tüccarları ve ticari faaliyetlerini ortaya koyabilmektir. Çalışma sonucunda, Osmanlı İmparatorluğu’nun başkentindeki Fransızların kendilerine özgü bir koloni oluşturarak ticaretlerini komisyoncu-müvekkil mekanizmasıyla güvence altına aldıkları belirlenmiştir. Ayrıca Fransa’daki birkaç tüccar aile şirketinin arşivleri üzerinden 17. yüzyılın ilk yarısına ait İstanbul ile ilgili değerli verilere ulaşılmıştır. Payitaht’taki Fransız tacir sayısının bu yüzyılda arttığı, ortaklıklar kurdukları ve ticarethaneler açtıkları tespit edilmiştir. Yürüttükleri yerel ve uluslararası ticarete dair Osmanlı mahkemelerine yansıyan hususlar da Fransızların Osmanlı medeniyetindeki yerini ve karşılaştıkları sorunları ortaya koymaktadır.

This study aims at discussing the French trade in Istanbul during 17th century by revealing the Ottoman and French sources from this century, to provide the researchers with new fields of study. The goal of the study is to explain the development process of the French trade in Istanbul, together with the names of the traders and the commercial activities performed by them. The study determines that the French people, who lived in the capital city of the Ottoman Empire, established their own colony and secured their commercial activities thanks to a broker-client mechanism. Moreover, we have found valuable data regarding Istanbul during the first half of the 17th century, by accessing the company archives of some of the family companies in France. It is determined that the number of French traders in the capital city increased during that century; they established various partnerships and opened places of business. What is more, the points stated in Ottoman court sources regarding the local and international commercial activities of the French people show their position within the Ottoman civilization, as well as the problems they experienced.
Keywords: 17. yy; 17th Century; Commerce; France; Fransa; French Trade in Istanbul; History; İstanbul’da Fransız Ticareti Ottoman-France Relations; Osmanlı-Fransa İlişkileri; Osmanlı-Fransa Ticareti; Ottoman-France Trade; Tarih; Ticaret